(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The era of Big Data has ushered in a paradigm shift in how we collect, process, and derive insights from vast and complex datasets. This abstract provides an overview of the key concepts, challenges, and opportunities associated with Big Data.Big Data refers to extremely large and diverse datasets that exceed the capabilities of traditional data processing methods. These datasets are characterized by the three Vs: Volume, Velocity, and Variety. Volume pertains to the massive scale of data generated from various sources, including social media, sensors, and transactions. Velocity refers to the rapid speed at which data is generated and must be processed to extract meaningful insights in real-time or near-real-time. Variety involves the diverse nature of data types, formats, and sources, such as structured, semi-structured, and unstructured data.The challenges posed by Big Data are multifaceted. Traditional data processing tools and techniques are inadequate to handle the scale and complexity of these datasets. Storage, processing power, and computational resources must be efficiently managed to derive value from Big Data. Additionally, issues of data quality, privacy, security, and ethical considerations come to the forefront, demanding robust strategies to ensure responsible data handling and usage.